Risk Management of Innovation Projects in the Context of Globalization - Nikolova, Liudmila V.; Kuporov, Juriy Ju.; Rodionov, Dmitriy G. (International Journal of Economics and Financial Issues, 2015)
Globalization is becoming increasingly important in the economy. It strongly influences the advanced technologies and innovation processes. The present stage of economic development differs from the preceding one by the increased role and autonomy in the innovation processes management that has led to the need for change in the approach to the application and development of innovation project risk management methods and techniques. The existing methods and ways of assessing and managing innovation project risks do not allow obtaining the maximum effect from their implementation. Therefore there was a need to develop new methods and techniques that would take into account the market conditions and the use of new financial instruments and strategies. The article considers the application of the system optimization method when building a risk management model for innovation projects in the context of globalization. Scientific novelty includes the development of a method and a model to calculate limiting values of factors, which bring the target value of the corresponding criterion of the innovation project efficiency to critical limit at the solution to direct and inverse problems. As a result, the authors have built a model of innovation project sustainability region in the context of globalization, using MATHCAT software (computer algebra system from a class of computer-aided design, focused on preparation of interactive documents with computations and visual tracking). Keywords: globalization, innovation project, sustainability model, sustainability method, risk factor, system optimization. JEL Classifications: C61; C63; F62; O33; O32